IMPACT OF VARIOUS LEVELS OF MEDICINAL PLANTS ON SOME PRODUCTIVE AND PHYSIOLOGICAL TRAITS IN BROILER CHICKENS - ARTOSHI, NECHIRVAN H.; TAYBE, IHSAN T.; SÖĞÜT, BÜNYAMIN (Journal of Duhok University, 2020)
A study aimed to evaluate the influence of using three medicinal plants on some productive and physiological traits of broiler chickens. Two hundred eighty-eight chicks (Ross 308) randomly distributed into eight groups with three replicates in each treatment. First group was fed the basal diet, without any plant supplement, as control group, while the 2nd and 3rd groups were fed the same diet with thyme (5 and 10 g/kg, respectively), the 4th and 5th groups were fed diets with Adiantum (3 and 5 g/kg, respectively) and the 6th and 7th groups were fed diets supplemented with rosemary at 5 and 10 g/kg, respectively, the combination of plants (7.5 g/kg of thyme and 7.5 g/kg of rosemary and 4 g/kg of adiantum) added to the basal diet of group 8th. The active compounds of the three plants were analyzed by Gas Chromatography/Mass Spectrometry. Live body weight was measured at weekly intervals. At the end of the experiment, the following traits were measured: carcass traits, internal organ, lymphoid organs and meat color. The obtained results summarized as follows: Fourteen, Fifteen and Twenty-one compounds were identified in the Thyme, Adiantum and Rosemary samples, respectively, and the major compounds were carvacrol (60.77%), gamma-terpinene (41.23%) and α-Pinene (51.87%), respectively. Overall, there is a significant effect of medicinal plants on live body weight in both genders, in which the male chicks in the 4th group and female chicks in 7th group had significantly higher live body weight. Regarding male chickens, T2, T3 and T8 groups have significantly higher carcass yield, also each of dressing percentage, breast, legs and wings were higher in T3 group. Furthermore, neck and back weight was higher in T3 group in both genders. It can be concluded that the supplementation of medicinal plants to broiler´s diet had a beneficial effect on most of broiler performance, particularly in male chickens that fed T3 group (Thyme 5g/kg).